2019
DOI: 10.18332/tid/114089
|View full text |Cite
|
Sign up to set email alerts
|

To text or not to text? Acceptability of WeChat and text messaging intervention to promote tobacco control assistance among parents who smoke in rural China

Abstract: INTRODUCTIONAlthough the use of mobile health (mHealth) to promote tobacco control and smoking cessation interventions has been available in developed countries, their use in low- and middle-income countries (i.e. in China) is lacking. This study examined the acceptance of text messaging and/or WeChat based tobacco control intervention among parents who smoke, in rural China.METHODSUsing a structured questionnaire, we surveyed smoker households (n=668) of children aged ≤5 years in two rural regions of southern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
0
4
1
Order By: Relevance
“…This might be because men are more task-orientated and more interested in new technology [ 32 , 33 ]. Moreover, inconsistent with the findings of earlier studies, we also found an association between acceptance of a text messaging intervention and educational levels, which was reflected by the high proportion of those with at least a college or university education in our study [ 16 , 34 ].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This might be because men are more task-orientated and more interested in new technology [ 32 , 33 ]. Moreover, inconsistent with the findings of earlier studies, we also found an association between acceptance of a text messaging intervention and educational levels, which was reflected by the high proportion of those with at least a college or university education in our study [ 16 , 34 ].…”
Section: Discussioncontrasting
confidence: 99%
“…On the other hand, a mobile intervention could be achieved through WeChat (a popular, multipurpose messaging, social media, and mobile payment app). There are more than 1.1 billion WeChat users in China [ 16 ]. Therefore, the intervention could offer an opportunity to extend the reach of tobacco cessation interventions outside of traditional health care settings via a mobile phone app that most adults already own, is generally always on, and is already used many times each day.…”
Section: Introductionmentioning
confidence: 99%
“…Research on methods and approaches to smoking cessation has developed in China as awareness of the hazards of smoking and the dangers of secondhand and thirdhand smoke have spread, which shows that the Chinese Government has realized the importance of smoking cessation 23 , especially with the development of information technology 24 , and more and more smokers who want to quit are trying electronic information system interventions for smoking cessation methods and approaches 25 . However, we still find that most of the concerns about the impact factors of smoking cessation focus on the perception of smoking harm and smoking cessation drugs usage instead of psychological intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Implementing smoking cessation interventions using WeChat may thus mitigate the lack of smoking cessation services in rural areas. Moreover, acceptance of social media-based interventions for tobacco cessation is high among rural smokers [28]. Smokers who lived in rural areas had better smoking cessation outcomes; however, the effectiveness of a WeChat-based intervention was only found in the urban area.…”
Section: Using Wechat To Mitigate the Difference Between Urban And Ruralmentioning
confidence: 99%